Explanation:
Let x be the first integer
Let y be the 2nd integer
Let z be the 3rd integer
Given
![x + y + z = 3y](https://img.qammunity.org/2022/formulas/mathematics/high-school/r1gf41l0lc0mpub9il2dkg12btf0u1d9ff.png)
Also given, x = 7, y = 8, z = 9, substitute x,y and z into equation.
![x + y + z = 7 + 8 + 9 \\ = 24](https://img.qammunity.org/2022/formulas/mathematics/high-school/4i3xrlcscuz3v4vg3yz4ufqdlxy9zm2gs9.png)
![3y = 3 * 8 \\ = 24](https://img.qammunity.org/2022/formulas/mathematics/high-school/7czfxpxy4as84e2b7j17oprg4aryxiyuqn.png)
Therefore,
x+y+z = 3y for x = 7, y = 8, z = 9.
Now lets take x = 3, y = 4, z = 5.
![x + y + z = 3 + 4 + 5 \\ = 12](https://img.qammunity.org/2022/formulas/mathematics/high-school/c74pjb706x0mdc4dfwf27rtvedf5ffqz53.png)
![3y = 3 * 4 \\ = 12](https://img.qammunity.org/2022/formulas/mathematics/high-school/4ykqq3osgfvwfv8up4x2ww8avti33cqzsa.png)
As you can see , x+y+z = 3y is true for any 3 consecutive numbers.